ANALYZE THE EFFECTIVENESS OF TWITTER AS AN EWOM MEDIA (STUDY ON TENSAYAA'S GROUP ORDER) - Sekar Nathasya Hermawan; Cecep Safa'atul Barkah; Arianis Chan; Pratami Wulan Tresna (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Electronic word of mouth is a form of marketing with a high credibility because it comes from consumers who have experience with related products. Electronic word of mouth is also quite effective because one individual with another individual does not need to meet face to face and can be easily found on any media. The purpose of this research is to find out how effective Twitter is as an electronic word of mouth media for Tensayaa group order business and what marketing strategies are suitable to increase Tensayaa group order electronic word of mouth on Twitter. The method in this research is descriptive quantitative, with purposive sampling, where the population of this research is the Twitter followers of Tensayaa group order, and a sample of 227 respondents was found with the minimum determination of respondents is determined using the slovin formula. This research was also tested for validity, reliability, and descriptive statistics. The results of this research show that Twitter is an effective social media for conducting electronic word of mouth processes in the Tensayaa group order business by being reviewed through seven measurement dimensions.